2016
DOI: 10.3892/ol.2016.5059
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects and mechanisms of Ganoderma extracts and spores oil

Abstract: Abstract. Ganoderma lucidum is a popular herbal medicine used in China to promote health. Modern studies have disclosed that the active ingredients of Ganoderma can exhibit several effects, including antitumor effects and immunomodulation. The present study evaluated the antitumor effects of self-prepared Ganoderma extracts and spores oil, and investigated the possible underlying mechanisms by observing the effects of the extracts and oil on topoisomerases and the cell cycle. The results showed that Ganoderma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Topoisomerases I and II may be the target of GEs and GSO actions. 72 Triterpenoids plays an important role in the antitumor activity of Ganoderma. Wu et al isolated two new triterpenoids from G. lucidum, lucidenic acid N (162) and methyl lucidenate F (173).…”
Section: Antitumour Activitymentioning
confidence: 99%
“…Topoisomerases I and II may be the target of GEs and GSO actions. 72 Triterpenoids plays an important role in the antitumor activity of Ganoderma. Wu et al isolated two new triterpenoids from G. lucidum, lucidenic acid N (162) and methyl lucidenate F (173).…”
Section: Antitumour Activitymentioning
confidence: 99%
“…57 Nevertheless, in vitro studies have shown that they inhibit cancer cells and show high cytotoxic activities. 5,16,47,49 It has been shown in these studies that G. lucidum has played an important role in cancer treatment and prevention.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…50 Many studies showed that G. lucidum triterpenoids present cytotoxicity against cancer cells, have antioxidant effect and reduce cell damage. 5,16,47,[51][52][53] antimetastatic activity…”
Section: Cytotoxic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Previous study revealed that GLS oil prevented murine sarcoma S180 and murine hepatoma H22 tumor growth, ultimately inducing G1 cell cycle arrest. 16,17 In addition to the anticancer function of G. lucidum , its immune-enhancing effects have garnered increasing attention from researchers worldwide. 15,18 G. lucidum was found to significantly enhance natural killer (NK) cell activity in patients with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%